Celecoxib attenuates interleukin 33-induced expression of vascular cell adhesion molecule-1 in human ovarian endometriotic stromal cells - Ta-Chin Lin; Kai-Hung Wang; Kuo-Hsiang Chuang; An-Pei Kao; Tsung-Cheng Kuo (Elsevier, 2024)
Objective: Endometriosis is an estrogen-dependent chronic inflammatory disease in women of reproductive age. A review of the literature revealed that cytokines and inflammatory factors are associated with endometriosis-associated infertility. Interleukin 33 (IL-33) is a strong inducer of other pro-inflammatory cytokines. Vascular cell adhesion molecule-1 (VCAM-1) plays a central role in recruiting inflammatory cells, whose expression facilitates leukocyte adhesion and is rapidly induced by pro-inflammatory cytokines. Many studies have indicated that VCAM-1 expression is high in endometriosis; however, whether the expression of VCAM-1 is related to IL-33 is unclear. Materials and methods: Human ovarian endometriotic stromal cells (hOVEN-SCs) were treated with IL-33 to enable investigation of cell characterization, gene and protein expression, and signal pathways. Proliferation potential was measured using an MTT assay. Gene expression was analyzed using reverse transcription-polymerase chain reaction. Protein expression assay was performed using western blot analysis. Results: This study investigated the effects of IL-33 on VCAM-1 and COX-2 expression in hOVEN-SCs. First, the results revealed that the IL-33/ST2/mitogen-activated protein kinase (MAPK) signaling pathway could increase the expression of VCAM-1 and COX-2 in hOVEN-SCs. Second, we discovered that COX-2 expression was essential for IL-33-induced VCAM-1 expression because the effects could be negated through NS398, a selective COX-2 inhibitor. Finally, treatment of IL-33-treated hOVEN-SCs with celecoxib significantly and dose-responsively decreased VCAM-1 expression. Conclusion: Taken together, these results indicate that IL-33 can upregulate VCAM-1 expression in hOVEN-SCs through the IL-33/ST2/MAPK/COX-2 signaling pathway and thereby contribute to endometriosis.